Inventory of Disease Modeling, Health Planning, Budgeting, Costing and Resource Allocation Tools, and Health Information System Platforms - Vu, Lung Duy (World Bank, Washington, DC, 2022)
This rapid review of Disease Modeling, Health Planning, Budgeting, Costing & Resource Allocation Tools, and Health Information System Platforms aims to provide an overview of each of the specific platform and its intended use and capacity. This will ultimately help health implementers understand what tools are readily available and can be used or rapidly modified to suit their needs. In case a new tool is developed, this will help inform the key features that new tool should have. This review included tools that have had an established presence and use in low- and middle-income countries (LMIC) and are open access, including all HIV program planning and allocative efficiency (AE) tools conduced by the World Bank in 2016, major HIS tools from the “Global Goods Guidebook” published by Digital Square in 2019 and additional tools supported by major donors including USAID,DFID, the Bill & Melinda Gates Foundation, and UN agencies.